Advanced Doherty Power Amplifier Architectures for 5G Handset Applications: A Comprehensive Review of Linearity, Back-Off Efficiency, Bandwidth, and Thermal Management - Shihai He; Huan Chen (Chips, 2025)
This paper presents a comprehensive review of GaAs HBT-based Doherty power amplifiers (DPAs) targeting 5G New Radio (NR) handset applications. Focusing on the critical challenges of linearity enhancement, back-off efficiency improvement, bandwidth extension under low-voltage (3.4 V) operation, and chip thermal management, the authors analyze state-of-the-art DPAs published in recent years. Key innovations including dynamic power division technique, third order intermodulation (IM3) cancellation technology, and compact output combiners are comparatively studied. Using 5G NR signals, the critical performance of the latest reported PA such as maximum linear power, back-off efficiency, bandwidth, and operating voltage are quantitatively investigated. The measurement results demonstrated that the best performance in recent DPAs achieved high linear power of 31 dBm with 34% PAE and 30 dBm with 31% PAE at the N78 and N77 bands, respectively. The corresponding adjacent channel leakage ratios (ACLRs) were lower than −36.5 dBc without digital pre-distortion (DPD). This review provides a comprehensive understanding of the latest advancements and future directions in highly efficient and linear DPA designs for 5G handset front-end modules.